2023
DOI: 10.1002/aws2.1338
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sequential dosing of potassium permanganate for microcystin‐LR removal

Abstract: Permanganate can be scavenged by dissolved organic matter (DOM), which decreases microcystin (MC) removal efficiency, and permanganate attack on cyanobacterial cells can damage cells, resulting in the release of additional MCs. Here, the impact of sequential permanganate doses on MC‐LR removal in the presence of two DOM isolates (terrestrial‐ and algal‐derived) was examined. Although sequential permanganate dosing reduced the competition for permanganate from each DOM isolate, the overall MC removal efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Potassium permanganate has been identified as an oxidant of interest, but dissolved organic matter can affect its ability to oxidize microcystins. Hurd et al (2023) presented an evaluation of a sequential permanganate dosing strategy to potentially decrease the competition of dissolved organic matter for permanganate oxidant, minimize cell lysis to avoid release of additional microcystins, and oxidize microcystins. Findings of this study concluded that sequential dosing was less effective at oxidizing microcystins compared with a single higher dose, but that this strategy may be effective in source waters with low concentrations of highly competitive organics.…”
Section: Treatabilitymentioning
confidence: 99%
“…Potassium permanganate has been identified as an oxidant of interest, but dissolved organic matter can affect its ability to oxidize microcystins. Hurd et al (2023) presented an evaluation of a sequential permanganate dosing strategy to potentially decrease the competition of dissolved organic matter for permanganate oxidant, minimize cell lysis to avoid release of additional microcystins, and oxidize microcystins. Findings of this study concluded that sequential dosing was less effective at oxidizing microcystins compared with a single higher dose, but that this strategy may be effective in source waters with low concentrations of highly competitive organics.…”
Section: Treatabilitymentioning
confidence: 99%